Film Appreciation Movement in Jaffna - Raguram, S.; Thivakar, T. (Proceedings of the 4th Jaffna University International Research Conference (JUICe2018), 2018)
The appreciation or consumption of cinema had been grown in different platforms in diverse ways in Jaffna. The cinema appreciation in Jaffna consists of multi-dimensions and changes. These aspects remain very complex to date and the study was conducted in order to explore and understand the complexity. This subject should be studied in a long run. Hence, the scope of this study approached the research field of appreciation of cinema in Jaffna from different perspectives. The art of film appreciation exists in a different manner among different strata. Since the time the cinema was introduced to Jaffna, there were many changes that occurred in the taste of cinema as well. When we look at the cinema field in Jaffna many movements include audience clubs, forums for social works, film circles and film movements from time to time. These movements keep forming and vanishing throughout the history of Jaffna. This study was conducted in view of understanding the influence these movements had on the appreciation of cinema. The study further intended to determine whether the appreciation of cinema formed in Jaffna presented alternative platforms of appreciation was the sub-objective of this study. The study employed both quantitative and qualitative research methods. Interviews and focus group discussions were conducted among film reviewers, audience, and members of audience forums live in Jaffna to obtain data and information. The study found out that the Film Appreciation Movements were not started at the beginning in the public sphere and these movements were emerged and vanished on a temporary basis. Even though cinema appreciation in Jaffna evolved from individual appreciation to a movement, this movement was not sufficiently made people-oriented and it was not functioning in a public sphere too. The appreciation towards cinema in Jaffna spread from watching movies, commenting on them, and reviewing to social and political spaces. When we consider the political impact of film appreciation, the appreciation movement mobilized the audience towards popular and alternative politics. Apart from that these movements contributed to loving the public on social platforms, helping the public etc. Film appreciation created interest among the public in the ways in which movies are made. Rather than mere watching, the individual cinema appreciation created interest in the ways of film making, the study reveals.
Keywords: Film Appreciation; Film Circles; Public Sphere